Using MATLAB for Teaching Physics, Direct Current Circuits Problems Case Study - Isidor Kokalari; Kosta Lili (Science Education International)
Physics, even though it is guided by simple principles, tends for many topics to be obscured in the mathematics redundancy. MATLAB®, as interactive software for computer algebra, has already had an important impact on the way physics is taught by educators. It has also had a substantial impact on the way research is performed by students to overcome the detention of mathematical difficulties. The literature comparing MATLAB® with other programming languages used in teaching is addressed here in brief, along with the reasons why we choose MATLAB®. This paper aims to introduce, through some examples, the convenience of using MATLAB®, bothfor teaching and learning physics, by taking advantage of its computation power so that one can concentrate on applying the principles of setting equations instead of the technical details of solving equations. Some examples found in physics textbooks are analytically solved. We have developed MATLAB® codes regarding these examples as special cases that can be generalized for analyzing electrical direct current circuits. We conclude that the user-friendly environment of MATLAB®, with its powerful built-in routines for a variety of computations, is an effective tool to teach circuit analysis to physics students.